KOORDINASI PELAYANAN TINDAK KEKERASAN PADA ANAK DI KOTA PEKANBARU - Nasrul, Disa Gushilda; ", Zulkarnaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Violence against children is one of the biggest problems that occurs in the city of pekanbaru. Therefore the Department of women’s empowerment and child protection in collaboration with P2TP2A in pekanbaru which serves to facilitate the provision of various physical and non-physical devices to women and children victims of violence. In an effort to protect women and children there are several agencies that are involved and coordinate with each other. Coordination is an important role in one organization to achieve the same goals and wants to be achieved. This study aims to get an overview of coordination between P2TP2A city of Pekanbaru with relevant agencies and identify the factors that in fluency the coordination of violence services for children in Pekanbaru. This study used descriptive qualitative methods. This uses the coordination, communication of division of labour and discipline. From the results of the study, it was found that the coordination between P2TP2A and the related agencies was not optimal, seen through several coordination indicators, one of which is a form of direct communication in the form of a coordination meeting which is only carried out according to the needs of the case, and at meetings where leaders are often represented so as to cause ineffective coordination meetings that are produced because decisions in meetings must wait for leadership approval, and disciplinary indicators on coordination established by P2TP2A often cannot fulfill calls from the police as a psychological companion to the victim, due to the constraints, limited competent human resources and limited facilities and infrastructure. Therefore, coordination can be carried out with optimal support from the government in the form of an adequate budget for fulfillment of cases and the need for facilities and infrastructure. Keywords: Coordination of services, Child Abuse